Efficacy of Low Intensity Laser Therapy for Carpal Tunnel Syndrome: Experience of 54 Cases in Bangladesh - Chhobi, Farida Khatun; Abedin, Md Mamunul; Happy, Bijoya Dey; Yusuf, Md Abdullah; Hussain, Mohammad Enayet; Islam, Rafiqul (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: Management of the carpal tunnel syndrome (CTS) is very crucial for the clinical outcomes of the patients. Objective: The purpose of the present study was to assess the effectiveness of low intensity laser therapy (LILT) for the management of carpal tunnel syndrome patients. Methodology: This single centered, parallel, single blinded randomized control trial was conducted in the Department of Physical Medicine and Rehabilitation at National Institute of Neurosciences & Hospital, Dhaka, Bangladesh from January 2019 to June 2019 for a period of six months. All the Nerve Conduction Study (NCS) test confirmed cases of CTS patients with the age group of more than 18 years in both male and female were selected as study population. Patients who received regular nonsteroidal anti-inflammatory drugs or corticosteroids, patients treated with therapeutic modalities before, acute wrist trauma and surgery, cervical radiculopathy, thoracic outlet syndrome, tumor or infectious diseases, pregnancy, and any serious heart, liver or kidney diseases were excluded from this study. Patients were randomly assigned into two groups designed as group A and group B. The assignment was done with single blind method. Group A underwent laser therapy (3 Joules/cm2, 50 Hz, 2 min) over the carpal tunnel area. Group B were treated with conventional method. All patients received therapy for a total of 14 sessions, first 7 sessions on consecutive 7 days, and last 7 sessions on alternate days. Patients also used a wrist splint each night, practiced therapeutic exercises for CTS, and followed ADL advices. Patients were assessed according to BCTQ, Boston Carpal Tunnel Questionnaire. Result: Male-Female distribution was 9% & 91% respectively. Total score of SSS was 26.35±5.94 and 13.70±1.78 in baseline and after 6 weeks follow up respectively (p < 0.001) in group A. In group B, total score of SSS was 28.19 ±7.35 and 18.22 ± 5.63 in baseline and after 6 weeks follow up respectively (p < 0.001). In group A, FSS was initially 18.1, which was improved to 9.15 in 6 weeks; whereas in group B, FSS was improved from 18.86 to 11.25. The pain, numbness and paresthesia also significantly changed after 6 weeks follow up in laser therapy group. Conclusion: Low intensity laser therapy has superior clinical effectiveness at 6 weeks compared with night-resting splints in mild or moderate CTS. Journal of National Institute of Neurosciences Bangladesh, July 2021, Vol. 7, No. 2, pp. 103-107